Ocular surface sensitivity repeatability with cochet-bonnet aesthesiometer - Chao, Cecilia; Stapleton, Fiona; Badarudin, Noor Ezailina; Golebiowski, Blanka (American Academy of Optometry, 2015)
Purpose. To determine the repeatability of ocular surface threshold measurements using the Cochet-Bonnet esthesiometer on the same day and 3 months apart. Methods. Two separate studies were conducted to determine the repeatability of ocular surface threshold measurements made on the same day (n = 20 subjects) and 3 months apart (n = 29 subjects). The Cochet-Bonnet esthesiometer was used to measure corneal and inferior conjunctival thresholds using the ascending method of limits. The pressure exerted by the Cochet-Bonnet esthesiometer was determined using an analytical balance, for both the 0.08- and 0.12-mm-diameter filaments. This calibration was then used to convert filament length measurements to pressure. Repeatability was determined using a Bland and Altman analysis. Results. The pressure exerted at each filament length differed between the two filament diameters. The measured pressure also differed from values provided by the manufacturer. Repeatability of threshold measurements at the central cornea was shown to be good, with better repeatability for same-day measurements (coefficient of repeatability [CoR] = T0.23 g/mm2) than for those 3 months apart (CoR = T0.52 g/mm2). Threshold measurements at the inferior conjunctiva, in contrast, were poorly repeatable (CoR = T12.78 g/mm2). Conclusions. Cochet-Bonnet esthesiometry is repeatable when performed on the central cornea on the same day and 3 months apart, but this instrument is not recommended for conjunctival threshold measurements. (Optom Vis Sci 2015;92:183Y189) Key Words: Cochet-Bonnet esthesiometer, repeatability, ocular surface sensitivity, corneal mechanical threshold, conjunctival mechanical threshold